Factors Related To The Incidence of Cesarean Section Surgical Site Infection (CS SSI) At Harapan Jayakarta Hospital In 2019 - Novelia, Shinta; Aulya, Yenny; Agustini, Dini (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Chi square test results showed that there was a relationship between age and the incidence of CS SSI (p = 0.011), there was no relationship between parity and the incidence of CS SSI (p = 0.237), there was a relationship between education and the incidence of CS SSI (p = 0,000), there was a relationship between BMI with the incidence of CS SSI (p = 0.006), there was a relationship between DM and the incidence of CS SSI (p = 0,000), there was a relationship between anemia with the incidence of CS SSI (p = 0,000), and there was a relationship between prophylaxis antibiotic and the incidence CS SSI (p = 0.01). There was a relationship between age, education, BMI, DM, anemia and prophylactic antibiotics with the incidence of CS SSI. There was no relationship between parity and CS SSI.